Measuring resilience to childhood maltreatment in college students - Shirley, Lauren A., author; Rosen, Lee, advisor; Biringen, Zeynep, committee member; Bloom, Larry, committee member; Gibbons, Alyssa, committee member (Colorado State University. Libraries, 2010)
This study developed and validated three measures to he used in the assessment of outcomes for college students with childhood maltreatment histories. The College Adjustment Questionnaire (CAQ) measures college adjustment within academic, social, and emotional domains. The Childhood Maltreatment Questionnaire (CMQ) assesses for five types of child maltreatment - physical, sexual, and emotional abuse, and physical and emotional neglect. The Social/Emotional Resources Inventory (SERI) is a measure of protective factors typically associated with good outcomes for individuals who experience early adversity. Results of the confirmatory factor analyses, along with reliability and validity analyses, indicate that the measures demonstrate good psychometric properties and present an alternative to the use of the proprietary measures that currently exist. Future studies will need to further validate the measures, particularly with regard to criterion-related validity. Additional studies should also examine the data obtained from the measures and use it to develop an understanding of the relationship between childhood maltreatment and college adjustment, as well as the protective factors that influence this relationship.
Covers not scanned.
Keywords: Adult child abuse victims; Resilience (Personality trait)